Regulatory B Cell Therapy in Kidney Transplantation - Garcia, Sergio G.; Sandoval-Hellín, Noelia; Franquesa, Marcella (Frontiers in Pharmacology, 2021)
In the context of kidney injury, the role of Bregs is gaining interest. In a number of autoimmune diseases, the number and/or the function of Bregs has been shown to be impaired or downregulated, therefore restoring their balance might be a potential therapeutic tool. Moreover, in the context of kidney transplantation their upregulation has been linked to tolerance. However, a specific marker or set of markers that define Bregs as a unique cell subset has not been found and otherwise multiple phenotypes of Bregs have been studied. A quest on the proper markers and induction mechanisms is now the goal of many researchers. Here we summarize the most recent evidence on the role of Bregs in kidney disease by describing the relevance of in vitro and in vivo Bregs induction as well as the potential use of Bregs as cell therapy agents in kidney transplantation.